Does the Elimination of Export Requirements in Special Economic Zones Affect Export Performance? : Evidence from the Dominican Republic - Defever, Fabrice (World Bank, Washington, DC, 2016)
Special economic zones, one of the most important instruments of industrial policy in developing countries, often feature export share requirements. That is, firms located in these zones are obliged to export more than a certain stated share of their output to enjoy the wide array of incentives available there, a practice prohibited by the World Trade Organization. This paper exploits the staggered removal of export requirements across products and over time in the special economic zones of the Dominican Republic to evaluate whether the importance of exports originating from the zones was affected by the elimination of export requirements. The findings show that entry increased among firms in special economic zones, while the average value of export transactions fell for existing exporters following the reforms. At the same time, continuous exporters were unaffected by the policy change, possibly because these firms were not constrained by the export requirement. Overall, special economic zones became more important with respect to the number of exporters based there but not in terms of the value of exports. The findings suggest that the elimination of performance requirements made it more attractive for firms to be based in special economic zones.